Resilience Assessment as a Tool for Understanding the Amazon Frontier as a Social-Ecological System - Buschbacher, Robert; Athayde, Simone; Bartels, Wendy-Lin; Mello, Ricardo (Sustainability in Debate, 2016)
This article introduces resilience thinking and a methodology for Resilience Assessment that consists of defining the system (key issue and system boundaries in time and space); looking at history (timeline and cross-scale drivers and interactions); specifying resilience of what to what (defining attributes and variables); scenarios (likely future drivers and possible desirable and undesirable future regimes); and developing management considerations to promote desirable scenarios. Resilience assessment for three major social groups of Cotriguaçu municipality in Mato Grosso, Brazil – medium to large landholders, the Rikbaktsa indigenous people, and family farmers – found that each social group has gone through multiple iterations of the growth-collapse-reorganization adaptive cycle and that the dynamics of this system are largely determined by economic and policy drivers that come from a larger scale. Contributions to the resilience assessment methodology are to base the analysis of the system on its historical trajectory, seek to explicitly incorporate the perspectives of local actors, and use scenario analysis to develop possible management interventions.